Chapter 8: Negotiating a (Border Literary) Community Online en la línea. - Fallon, Paul (Latin American Cyberculture & Cyberliterature, 2007)
Chapter 8 of the book "Latin American Cyberculture and Cyberliterature," edited by Thea Pitman and Claire Taylor is presented. It explains how new artists react to and develop the changing temporalities afforded by the new media. It also notes a conflict between such artists' thinking through online possibilities and the practices they put into effect. The effects of the evolution of blogging along the northern Mexican border on the communities invoked are also discussed.